Strengthening Character Education through Management of Religious Habits Program for Students: Penelitian - Sri Erna Nurmalia (PT PUSTAKA CENDEKIA GROUP, 2026)
Character education is an important part of Islamic education to shape students with noble character. One of the efforts undertaken by madrasas is through a religious habituation program that is implemented continuously. This study aims to describe the strengthening of character education through the management of the religious habituation program for students at MTs Al Ikhlas Cibalong Tasikmalaya. This study uses a qualitative approach with a case study method. Data were obtained through observation, interviews, and documentation, then analyzed using the Miles, Huberman, and Saldaña model which includes data condensation, data presentation, and drawing conclusions. The results show that the management of the religious habituation program is carried out through structured planning, organization, implementation, and evaluation. The religious habituation program is realized through activities such as tadarus Al-Qur'an, joint prayers, congregational prayers, and other religious activities supported by the Islamic boarding school environment. The program has a positive impact on the formation of religious character, discipline, responsibility, and politeness in students. Thus, the religious habituation program is an effective means of strengthening the character education of students at MTs Al Ikhlas Cibalong Tasikmalaya.